2018
DOI: 10.1037/int0000101
|View full text |Cite
|
Sign up to set email alerts
|

The first sessions of psychotherapy: A qualitative meta-analysis of alliance formation processes.

Abstract: Although the effect of the therapeutic alliance on psychotherapy outcome is well documented in the research literature, less is known about how the alliance is developed during the first sessions of therapy. This qualitative meta-analysis aimed to summarize and reanalyze the existing qualitative research literature on alliance-formation processes from the perspectives of therapists and clients. Research articles were obtained through systematic searches in the following databases: PsycINFO, MEDLINE, and Web of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 59 publications
(106 reference statements)
3
27
0
Order By: Relevance
“…Which experiences were relevant for therapy (theme three) and how can one find a way of working with personal issues, while at the same time not being too critical or disloyal to loved ones (theme four). These results underscore how coming to a therapy process is connected to apprehension and a need to discover what the social rules of the situation are, a point recently emphasized in a qualitative meta-analysis of clients' experiences with starting therapy from an alliance formation perspective (Lavik et al, 2018).…”
Section: Discussionmentioning
confidence: 72%
“…Which experiences were relevant for therapy (theme three) and how can one find a way of working with personal issues, while at the same time not being too critical or disloyal to loved ones (theme four). These results underscore how coming to a therapy process is connected to apprehension and a need to discover what the social rules of the situation are, a point recently emphasized in a qualitative meta-analysis of clients' experiences with starting therapy from an alliance formation perspective (Lavik et al, 2018).…”
Section: Discussionmentioning
confidence: 72%
“…Our findings suggest that the relationship may serve as a foundation underpinning client participation. Similarly, a recent meta‐analysis of all qualitative alliance formation studies, from both patient and therapist perspective, underscores how supporting agency from the therapist perspective, and gaining hope and strength through feeling accepted from the patient perspective, are important micro‐processes in developing a productive working alliance (Lavik, Frøysa, Brattebø, McLeod & Moltu, ). Our findings suggests that mental health services need to be tailored to the individual needs and preferences of young service users, and that attention to symptoms and distress needs to be balanced with a relational orientation.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis of qualitative studies of alliance formation from client and therapist perspectives, Lavik et al (2018a) concluded that clients express needs for therapists who are competent professionally to provide problem-solving strengths and hope, while also helping in overcoming initial fears and apprehension with personal warmth and tolerance. Therapists in this meta-analysis emphasized that they worked continuously to combine technical interventions with interpersonal warmth.…”
mentioning
confidence: 99%